Association between the ACE insertion/deletion polymorphism and pterygium in Sardinian patients: a population based case–control study. Issue 10 (23rd October 2014) - Demurtas, Paolo; Orrù, Germano; Coni, Pierpaolo; Minerba, Luigi; Corrias, Michela; Sirigu, Paola; Zucca, Ignazio; Demurtas, Elena; Maxia, Cristina; Piras, Franca; Murtas, Daniela; Lai, Simone; et al.
Abstract : Objective: The purpose of the study was to examine whether the insertion (I) and/or deletion (D) polymorphism of ACE confers susceptibility to primary pterygium in Sardinian patients in a case–control study. Methods and results: Polymorphism genotyping was performed by nested PCR using genomic DNA extracted from the whole peripheral blood of participants with (n=251) and without (n=260) pterygium. DD, ID and II genotype frequencies were: 48%, 39% and 13%, respectively, for patients with pterygium, and 15%, 40% and 44%, respectively, for the control group. A statistically significant difference was found between the pterygium and control groups for the ACE I/D polymorphism (p<0.001). Moreover, a statistically significant difference was found between the DD and II groups (p<0.01; OR=10.49; 95% CI 6.18 to 17.79), DD+ID versus II group (p<0.01; OR=5.23; 95% CI 3.37 to 8.13) and DD versus ID groups (p<0.01; OR=3.21; 95% CI 2.04 to 5.04). Conclusions: Statistical analysis showed that the DD genotype is associated with an increased risk of developing pterygium, and with a good chance that the D allele may play an important role in the development of disease.